Aid to Jobless Workers in Florida in the Face of the Great Recession: The Interaction of Unemployment Insurance and the Supplemental Nutritional Assistance Program - Colleen M. Heflin; Peter R. Mueser (Institute for the Study of Labor (IZA), 2013)
Although many programs redistribute resources in the U.S., two program were central in providing a safety net for those facing hardship during the Great Recession: the Supplemental Nutrition Assistance Program (SNAP), which grew to 47.7 million people in January 2013 or 15.1 percent of all Americans and the Unemployment Insurance Program (UI), which more than doubled with the onset of the recession, reaching a seasonally adjusted maximum of 6.5 million recipients in June 2009. We examine state administrative data from Florida for SNAP and UI from late 2005 through early 2010. We focus on two research questions: 1. In the face of caseload growth and compositional change in both programs, how has joint participation in UI among SNAP recipients changed? How much of the increase in joint participation is driven by changes in the characteristics of individuals participating in SNAP? How much is driven by the changing economic and policy conditions? 2. How has the role of UI changed for SNAP participants, and in particular how have patterns of combined usage evolved during this period? We find that the number of families relying on both SNAP and UI together ballooned with the Great Recession, and that the patterns changed as expected, with UI growing dramatically in relative importance. At the same time, only a minority of those swelling the ranks of SNAP obtained benefits from the UI program, suggesting that the current safety net has important limitations in times of serious economic distress.
Keywords: H24; H53; I38; J65; 330; Great Recession; social insurance; safety net; SNAP; Unemployment Insurance